Recent advancements in smart responsive tissue adhesives for medical applications - Lin, Shiqi; Jin, Qiang; Wang, Ji; Wu, Sufan; Zhou, Yi (Frontiers in Medicine, 2025)
Bioadhesives have emerged as a promising alternative to conventional sutures, offering rapid and robust tissue integration while overcoming limitations such as time-consuming procedures and risks of secondary tissue damage. However, the bonding strength and degradation kinetics of most existing adhesives remain difficult to precisely control, limiting their adaptability to diverse tissue types and clinical scenarios. In this context, smart responsive bioadhesives have attracted significant attention due to their tunable adhesion properties, on-demand detachment capability, and tissue-matching mechanical properties. These materials can respond to biological environmental stimuli, enabling dynamic interactions with biological systems and opening new avenues for applications in wearable devices, controlled drug delivery, tissue repair, and smart bioelectronic interfaces. Nevertheless, a systematic review summarizing the synthesis strategies, adhesion mechanisms, and application prospects of such advanced adhesives remains lacking. Herein, we comprehensively analyzes the design strategies, working principles, and biomedical applications of smart responsive adhesives over the past decade. Furthermore, we discuss current limitations and propose future directions aimed at accelerating the translation of smart responsive adhesives from laboratory research to clinical practice. This review aims to provide a comprehensive understanding of these materials and offer valuable insights for researchers engaged in developing advanced tissue adhesives for practical applications.